Plasticity Through Canalization: The Contrasting Effect of Temperature on Trait Size and Growth in Drosophila - McDonald, Jeanne M. C.; Ghosh, Shampa M.; Gascoigne, Samuel J. L.; Shingleton, Alexander W. (Frontiers in Cell and Developmental Biology, 2018)
In most ectotherms, a reduction in developmental temperature leads to an increase in body size, a phenomenon called (known as) the temperature size rule (TSR). In Drosophila melanogaster, temperature affects body size primarily by affecting critical size, the point in development when larvae initiate the hormonal cascade that stops growth and starts metamorphosis. However, while the thermal plasticity of critical size can explain the effect of temperature on overall body size, it cannot entirely account for the effect of temperature on the size of individual traits, which vary in their thermal sensitivity. Specifically, the legs and male genitalia show reduced thermal plasticity for size, while the wings show elevated thermal plasticity, relative to overall body size. Here we show that these differences in thermal plasticity among traits reflect, in part, differences in the effect of temperature on the rates of cell proliferation during trait growth. Counterintuitively, the elevated thermal plasticity of the wings is due to canalization in the rate of cell proliferation across temperatures. The opposite is true for the legs. These data reveal that environmental canalization at one level of organization may explain plasticity at another, and vice versa.